The Impact of Adjuvant Radiotherapy on Clinical Performance Status in Patients With Grade II Spinal Cord Astrocytoma – A Nationwide Analysis by the Neurospinal Society of Japan - Ryo Kanematsu; Masaki Mizuno; Tomoo Inoue; Toshiyuki Takahashi; Toshiki Endo; Seiji Shigekawa; Jun Muto; Daisuke Umebayashi; Takafumi Mitsuhara; Kazutoshi Hida; Junya Hanakita (Neurospine, 2023)
Objective The impact of adjuvant radiotherapy on overall survival (OS) and progression-free survival (PFS) of patients with grade II spinal cord astrocytomas remains controversial. Additionally, the relationship between progression and clinical deterioration after radiotherapy has not been well investigated. Methods This study included 53 patients with grade II intramedullary spinal cord astrocytomas treated by either subtotal, partial resection or open biopsy. Their clinical performance status was assessed immediately before operation and 1, 6, 12, 24, and 60 months after surgery by Karnofsky Performance Scale (KPS). Patients with and without adjuvant radiotherapy were compared. Results The groups with and without radiation comprised 23 and 30 patients with a mean age of 50.3 ±22.6 years (range, 2–88 years). The mean overall disease progression rate was 47.1% during a mean follow-up period of 48.4 ±39.8 months (range, 2.5–144.5 months). In the radiation group, 11 patients (47.8%) presented with progressive disease, whereas 14 patients (46.7%) presented with progressive disease in the group without radiation. There were no significant differences in OS or PFS among patients with or without adjuvant radiotherapy. KPS in both groups, especially radiation group, gradually decreased after operation and deteriorated before the confirmation of disease progression. Conclusion Adjuvant radiotherapy did not show effectiveness regarding PFS or OS in patients with grade II spinal cord astrocytoma according to classical classification based on pathohistological findings.